Tao of statistics a path to understanding (with no math) - Keller Dana K (New Delhi Sage, 2006)
It provides a new approach to statistics through impressionistic illustrations, verse, and accompanying text.This text explains what statistics mean and how they are used rather than how to calculate them.
Keywords: Statistics; Statistics-philosophy